Implications of Tamarkoz on stress, emotion, spirituality and heart rate - Nasim Bahadorani (Nature Portfolio, 2021)
Abstract Perceived stress among university students is a prevalent health issue directly correlated with poor academic performance, poor sleep quality, hopelessness, compromised physical and mental health, high risk of substance abuse, and suicidal ideation. Tamarkoz, a Sufi meditation, may reduce the impact of stressors to prevent illness among students. Tamarkoz is the art of self-knowledge through concentration and meditation. It is a method of concentration that can be applied to any task. The method is said to discipline the mind, body, and emotions to avoid unintended distractions. Therefore, it can be used in daily life activities, such as studying, eating, driving, de-stressing or in Sufism, seeking self-knowledge. This study was an 18-week quasi-experimental design with pre-intervention, post-intervention and follow-up assessments in the experimental group, a wait-list control, and a third group that utilized the campus health center’s stress management resources. Participants, university students, had no prior exposure to Tamarkoz, and there were no statistically significant differences among groups on baseline measurements. Using a generalized linear mixed model, significant increases in positive emotions and daily spiritual experiences, and reductions in perceived stress and heart rate were found in the experimental group compared to the other two groups. Tamarkoz seems to show some advantages over the usual stress management resources offered by a student health center. Trial registration: ClinicalTrials.gov Protocol Registration Date: (03/04/2018); ClinicalTrials.gov ID: NCT03489148.